Brain changes in stroke patients during rehabilitation: a longitudinal study - Hongxing Wang; Xuejin Cao; Jia Quan; Hengrui Zhou; Yanli Liu; Wei Wang; Zan Wang; Shenghong Ju; Yuancheng Wang; Yijing Guo (Frontiers in Neuroscience, 2025)
BackgroundTemporal changes in brain structure and function following rehabilitation, and their relationship with positive recovery in stroke patients experiencing hemiplegia, remain unclear. This study used multimodal magnetic resonance imaging (MRI) to investigate the longitudinal changes in the brains of stroke patients with good outcomes after motor rehabilitation.MethodsEight subcortical ischemic stroke patients with hemiplegia were enrolled. Multimodal MRI data and clinical assessments were collected in the stable post-acute period and at a 3-month follow-up. Functional connectivity (FC) was calculated for motor-related regions of interest (ROIs) based on functional MRI data. Gray matter volumes (GMVs) and diffusion tensor imaging (DTI) parameters were analyzed to evaluate the temporal changes during recovery.ResultsCompared with initial scans, follow-up scans revealed FC changes between several brain regions, e.g., FC increased between the ipsilesional thalamus and the contralesional middle temporal gyrus (MTG). Increased GMV was observed in the contralesional MTG, while GMV decreased in the contralesional cerebellum, correlating with Action Research Arm Test (ARAT) scores at follow-up.ConclusionThe findings suggest that MTG is a key area for neuronal activation and functional reconstruction in stroke patients during motor recovery. These results deepen our understanding of the imaging manifestations of structural and functional neural remodeling during rehabilitation.